Multiple Contracts According to the Fatwa of National Sharia Council - Bukhoree Lateh (International Journal of Nusantara Islam, 2016)
At the recent decades, the business activity in Islamic Financial Institutions consists of funding, financing, and service. These are addressed to economic development and improving the society welfare. In the line of funding, the people can invest their money such saving and deposit. Uniquely, deposits may be withdrawn at any time with the use of checks, gyro, forms of payment order, or money transfer. But, not all gyro transactions can be justified by Islamic law (Sharia) in which uses the principle of sharia mutual benefit. Therefore, the National Sharia Council National Sharia Council of Indonesian Council of Ulama (NSC-ICU) deems it necessary to be set in the Fatwa mu’ā mala form that can be used as the guidelines for the implementation of current accounts in Sharia Banking Institution. It is referring to the National Sharia Board Fatwa DSN-MUI Number: 01/DSN-MUI/IV/2000). Based on the reason, this paper will explain the Implementation of Multiple Contract (al-'uqū d al-murakkaba) according to the fatwa of National Sharia Council.